The Effect of Satisfaction, Job Training and Non-Physical Work Environment on Employee Performance of PT Elnusa Tbk Jakarta - Khairunnisa Khairunnisa; Beureukat Beureukat; Melati Melati; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This research aims to analyze how much influence Job Satisfaction, Job Training and Non-Physical Work Environment on employee performance of PT Elnusa Tbk Jakarta. The method used in this research is descriptive quantitative. Data analysis of several tests, namely instrument test, multiple linear regression correlation analysis, model feasibility test and t test hypothesis testing with a total of 104 permanent employees with data collection methods through questionnaires. Data analysis was carried out using SPSS 25. The regression analysis results show Job Satisfaction, Job Training and Non-Physical Work Environment have a positive and significant effect on Employee Performance, which is shown in the coefficients table in the regression equation mode. The t test results show that job satisfaction, job training and non-physical work environment partially have a significant effect on employee performance. The results of the F test show that together the variables of Job Satisfaction, Job Training and Non-Physical Work Environment simultaneously have a significant effect on Employee Performance. The results of the Determination Coefficient Test (R2) from the Adjusted R Square value obtained the result of 62.6%. The results of this study are expected that PT Elnusa Tbk Jakarta can always improve and pay attention to Job Satisfaction, Job Training and Non-Physical Work Environment on Employee Performance.